2020
DOI: 10.3390/cancers12082172
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Timing of Health-Related Quality of Life Assessments on the Actual Results in Glioma Patients: A Randomized Prospective Study

Abstract: Background: The aim of this study was to explore the impact of the timing of Health-Related Quality of Life (HRQoL) measurements in clinical care on the obtained HRQoL scores in glioma patients, and the association with feelings of anxiety or depression. Methods: Patients completed the European Organisation for Research and Treatment of Cancer (EORTC)’s Quality of Life Questionnaires (QLQ-C30 and QLQ-BN20), and the Hospital Anxiety and Depression Scale (HADS) twice. All patients completed the first measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…During the second assessment, patients were randomly assigned to one of two groups: questionnaires were administered 1) before the consultation with the physician or 2) after the consultation with the physician. Further details on the study design and outcomes are described previously 18 . For this study, the outcomes of the first assessment (day of the MRI scan) were used for the primary analyses.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…During the second assessment, patients were randomly assigned to one of two groups: questionnaires were administered 1) before the consultation with the physician or 2) after the consultation with the physician. Further details on the study design and outcomes are described previously 18 . For this study, the outcomes of the first assessment (day of the MRI scan) were used for the primary analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Data was collected as part of a randomized prospective study measuring the impact of the timing of patient‐reported outcome assessments on the actual HRQoL outcomes in clinical care for glioma patients. 18 Patients were recruited in the Haaglanden Medical Center in The Hague, The Netherlands, between July 2016 and July 2018. Informed consent was obtained from all patients and their proxies included in the study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations